Development of Sustainability Assessment Tool for Malaysian hydropower industry: A case study - Faiz, Mohd Turan; Kartina, Johan; Muhammad Irfan, Abu Sofian (IOP Publishing, 2018)
This research deals with the development of sustainability assessment tools as a medium to assess the performance of a hydropower project compliances towards sustainability practice. Since the increasing needs of implementing sustainability practice, developed countries are utilizing sustainability tools to achieve sustainable development goals. Its inception within ASEAN countries including Malaysia is still low. The problem with most tools developed from other countries is that it is not very comprehensive as well as its implementation factors are not suitable for the local environment that is not quantified. Hence, there is a need to develop a suitable sustainable assessment tool for the Malaysian hydropower industry to comply with the sustainable development goals as a bridging gap between the governor and the practitioner. The steps of achieving this goal is separated into several parts. The first part is to identify sustainable parameters from established tools as a model for comparison to enhance new parameters. The second stage is to convert equivalent quantification value from the model to the new developed tools. The last stage is to develop software program as a mean of gaining energy company feedback with systematic sustainable reporting from the surveyor so as to be able to integrate sustainability assessment, monitoring and reporting for self-improved reporting.